"This Bright Inward Cinema of Thought" – Stream of Consciousness in Contemporary English Fiction - Strauß, Sara

‘Monstrous’ Homes: How Private Spaces Shape Characters’ Identities in 19th-century Sensation Fiction - Flotmann, Christina (Monstrous Geographies: Places and Spaces of the Monstrous)

Ambiguity in ‘Star Wars’ and ‘Harry Potter’: A (Post-)Structuralist Reading of Two Popular Myths - Flotmann, Christina

Populäre Mythen bei Star Wars und Harry Potter - Flotmann, Christina
Interview 2 Feb. 2013

Northern Landscapes and Anti-Thatcherite Positioning - Tönnies, Merle (Journal for the Study of British Cultures)

Feminising a Classical Male Plot Model? Black British Women Writers and the 'Bildungsroman' - Tönnies, Merle (International Journal of English Studies)

Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Spatial Representations of British Identities

A Bricolage of Identities in Crisis. Colour Photography Documenting Northern England under Thatcher - Tönnies, Merle (Facteurs d'Identité / Faktoren der Identität)

Introducing Narrative in Drama - Flotmann, Christina; Tönnies, Merle (Narrative in Drama: CDE Studies 18)

Narrative in Drama

Narrative in Drama

Reading British Spaces

Das englische Drama der Gegenwart: Kategorien-Entwicklungen-Modellnterpretationen

The Features of Meanings of Orality in Black British Performance Poetry - Tönnies, Merle; Sand, Andrea (Anglistentag 2009 Klagenfurt. Proceedings)

Transgressive Melodrama. The 'Sensational' 1860s and their After-Effects - Tönnies, Merle (Victorian Highways - Victorian Byways. New Approaches to Nineteenth-Century British Literature and Culture)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'A Map of the World' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Knuckle' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Plenty' - Tönnies, Merle (Kindlers Literaturlexikon)

Ann Patricia Jellicoe 'The Knack' - Tönnies, Merle (Kindlers Literaturlexikon)

Stephen Poliakoff 'Strawberry Fields' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Amadeus' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Equus' - Tönnies, Merle (Kindlers Literaturlexikon)

George Bernard Shaw 'Mrs Warren's Profession' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Mrs Henry Wood' - Tönnies, Merle (Kindlers Literaturlexikon)

Mary Elisabeth Braddon 'Lady Audley's Secret' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Lady Windermere's Fan' - Tönnies, Merle (Kindlers Literaturlexikon)

Alan Ayckbourn 'Woman in Mind' - Tönnies, Merle (Kindlers Literaturlexikon)

Wilkie Collins 'The Moonstone' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'East Lynne' - Tönnies, Merle (Kindlers Literaturlexikon)

Translating African Traditions and Identities. Black Poetry in Contemporary Britain - Tönnies, Merle (Cultures of Translation)

The Visual Strategies of Nineteenth-Century Melodrama - Tönnies, Merle (Anglistik & Englischunterricht 71)

Kulturelle Bedeutungen und Kontexte der indischen Küche in Großbritannien - Tönnies, Merle (Interkulturelle Mahlzeiten. Kulinarische Begegnungen und Kommunikation in der Literatur)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

The Frontiers of the Sea - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

A Nose By Any Other Name - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)

Introduction to the Study of British Culture - Tönnies, Merle; Voigt, Ulrich

London-Diversity and Myth - Tönnies, Merle (Viewfinder Special. Lese-und Arbeitsbuch für die gymnasiale Oberstufe)

Forms and Functions of Violence in Contemporary Black British Drama - Tönnies, Merle (Anglistentag 2005)

Foregrounding Boundary Zones. Martin Parr's Photographic (De-)Constructions of Englishness - Tönnies, Merle (Spatial Practices 1)

Percy Mtwa, Mbongeni Ngema and Barney Simon: Woza Albert! (1981) - Tönnies, Merle (Drama II)